Degradation of High‐Nickel‐Layered Oxide Cathodes from Surface to Bulk: A Comprehensive Structural, Chemical, and Electrical Analysis. Issue 36 (9th August 2020) - Ko, Dong‐Su; Park, Jun‐Ho; Yu, Byong Yong; Ahn, Docheon; Kim, Kihong; Han, Heung Nam; Jeon, Woo Sung; Jung, Changhoon; Manthiram, Arumugram
Abstract: Multiple applications of lithium‐ion batteries in energy storage systems and electric vehicles require highly stable electrode materials for long‐term battery operation. Among the various cathode materials, high‐Ni cathode materials enable a high energy density. However, cathode degradation accompanied by complex chemical and structural changes results in capacity and voltage fading in batteries. Cathode degradation remains poorly understood; the majority of studies have only explored the oxidation states of transition‐metal ions in localized areas and have rarely evaluated chemical degradation in complete particles after prolonged cycling. This study systematically investigates the degradation of a high‐Ni cathode by comparing the chemical, structural, and electrical changes in pristine and 500 times‐cycled cathodes. Electron probe micro‐analysis and X‐ray energy dispersive spectroscopy reveal changes in the Ni:O ratio from 1:2 to 1:1 over a large area inside the secondary particle. Electron energy loss spectroscopy analysis related to structural changes is performed for the entire primary particle area to visualize the oxidation state of transition‐metal ions in two dimensions. The results imply that the observed monotonic capacity fade without unusual changes is due to the continuous formation of the Ni 2+ phase from the surface to the bulk through chemical and structural degradation. Abstract : The degradation of the high‐Ni layered oxide cathode is systematically investigated by comparing a pristine and 500‐cycled full‐cell through analyzing the microstructural visualization of the structural, chemical, and electrical changes from micrometer‐scale to the nanometer‐scale. This reveals that the monotonic capacity fade is due to the continuous formation of Ni 2+ phase at the surface and bulk via chemical and structural degradation.